PERTANGGUNG JAWABAN PEJABAT PEMBUAT AKTA OTENTIK ATAU PEJABAT UMUM TERKAIT JUAL BELI TANAH YANG SUDAH ADA PENETAPAN LOKASI PENGADAAN TANAH - Handayani, Marini Tri; Gultom, Elisatris; Baraba, Badar (EKSEKUSI, 2023)
The legal relationship of Land Sale and Purchase in relation to land acquisition for public purposes, and the role and responsibilities undertaken by a Notary Public or Public Official, become highly significant. This is because the Notary Public bears the responsibility to ensure that the land being bought and sold is transferred in accordance with the prevailing legal regulations. This study aims to determine the Accountability of the Notary Public or Public Official regarding the implementation of Land Sale and Purchase that has a designated Land Acquisition location, and the Legal Certainty Aspect of Authentic Deeds from Land Sale and Purchase Created by the Notary Public or Public Official in relation to Land Sale and Purchase that has a designated Land Acquisition location. The research method employed is normative juridical, focusing on literature review, particularly analyzing the applicable legal provisions. The research is descriptive-analytical in nature, aiming to comprehensively depict the state of an object in a systematic manner. The research is carried out in two stages: Field Research and Library Research, with the goal of obtaining primary, secondary, and tertiary legal sources. The research findings indicate that the sale and purchase of land rights by a Public Official, who oversees the transfer process of an object designated as land for development for public purposes, results in the improper receipt of compensation costs by the wrong party. In this regard, the Notary Public or Public Official, in carrying out their duties, must adhere to legal regulations, exercise prudence, and avoid favoring any party in order to prevent any party from being disadvantaged in the process of transferring land rights that they have executed